2020
DOI: 10.3390/pharmaceutics12090820
|View full text |Cite
|
Sign up to set email alerts
|

Rheology by Design: A Regulatory Tutorial for Analytical Method Validation

Abstract: The increasing demand for product and process understanding as an active pursuit in the quality guideline Q8 and, more recently, on the draft guideline on quality and equivalence of topical products, has unveiled the tremendous potential of rheology methods as a tool for microstructure characterization of topical semisolid dosage forms. Accordingly, procedure standardization is a dire need. This work aimed at developing and validating a methodology tutorial for rheology analysis. A 1% hydrocortisone cream was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 60 publications
1
37
0
Order By: Relevance
“…e rheological properties of the gel formulations are correlated to the preparation process, the molecular weight of the incorporated polymer, and the degree of crosslinking [40]. Based on the findings of the present investigation, it could be said that the rheological property of the formulation could be easily applied topically as the increasing rate of shear to the formulation resulted in a decrease in viscosity [41]. erefore, to initiate a flow of the formulation, stress needs to be applied, which will facilitate easy spreadability over the topical area.…”
Section: Characterization Of the Lul-neg For Viscosity Ph Andmentioning
confidence: 61%
“…e rheological properties of the gel formulations are correlated to the preparation process, the molecular weight of the incorporated polymer, and the degree of crosslinking [40]. Based on the findings of the present investigation, it could be said that the rheological property of the formulation could be easily applied topically as the increasing rate of shear to the formulation resulted in a decrease in viscosity [41]. erefore, to initiate a flow of the formulation, stress needs to be applied, which will facilitate easy spreadability over the topical area.…”
Section: Characterization Of the Lul-neg For Viscosity Ph Andmentioning
confidence: 61%
“…Generally, the rheology of semisolid products is highly sensitive to alternations in the product microstructure, and therefore, detailed rheological characterization takes the central role in detection of the potential microstructure differences [ 22 , 24 ]. Furthermore, rheological characterization serves as a useful quality and stability indicator, which could provide additional information concerning batch variability, product sensorial properties (e.g., consistency, spreadability, and feel) and consequently patient compliance [ 22 , 25 ]. Hence, EMA defines specific rheological parameters that should be documented when characterizing the rheological profile of a given formulation.…”
Section: Demonstration Of Extended Pharmaceutical Equivalence Of Topical Semisolid Drug Productsmentioning
confidence: 99%
“…However, currently, there are no regulatory recommendations for the standardization, i.e., formal validation of this method. Hence, Simões and coworkers [ 25 ] tried to establish a practical approach for validation of the rheological analysis, including the rheometer qualification and the validation of numerous operational critical parameters for a rheology profile acquisition. The experimental results showed that the rheology measurement method can be successfully validated, proving its suitability to determine sameness/differences between the formulations.…”
Section: Demonstration Of Extended Pharmaceutical Equivalence Of Topical Semisolid Drug Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…The viscosity profile of a semisolid dosage form is highly linked with the product sensorial properties, such as consistency, spreadability and feel, which strongly impact patient compliance [11,15]. From a quality perspective, viscosity measurements can be regarded as not solely a monitoring tool during process development and stability assessment, but also as a performance indicating tool, since these attributes correlate with drug release and diffusion rate [14].…”
Section: White Smooth Emulgelmentioning
confidence: 99%